Oxynoe antillarum (MOLLUSCA, OXYNOIDAE) NO ESTADO DO CEARÁ, NORDESTE DO BRASIL. - Meirelles, Carlos A. O.; Filho, Hilton C. Galvão; Scramosin, Karina A.; Matthews-Cascon, Helena (Revista Nordestina de Zoologia, 2010)
Oxynoe antillarum Mörch, 1863 occurs in the region from Florida to Brazil (32.39 o N to 24 o S, 89 o W 0 o W) and bathymetry from 3 to 11m. The type locality is the island of St. Thomas, in Virgin Islands. In Brazil, it only had previous records in Pernambuco, Bahia, Sao Paulo and Rio de Janeiro. Sacoglossans is a marine gastropod group that feed on marine algae, marine plants, opisthobranch eggs and their ecology is poorly studied. There are about 300 described species worldwide and for Brazil, have been observed so far, 23 species in 6 families and 12 genera, most of them collected in the State of São Paulo, Southeast Brazil. This work presents the occurrence of Oxynoe antillarum in the State of Ceará, Northeast Brazil, in algae of the genus Caulerpa in the intertidal zone of rocky beaches of Pacheco (03o 41’ S e 38o 38’ W) and Pedra Rachada (03o 25’ S e 39o 02’ W). Contributions to the morphology of the shell and soft parts are presented.